(untitled) (Texas Journal of Medical Science, 2022)
Low awareness of patients about the rules for using orthopedic structures and caring for them negatively affects their quality of life, and also affects the increase in the incidence of the oral mucosa. Methods for the prevention and treatment of this pathology are proposed.